EFFECT OF BREED, AGE, AND SEX ON QUALITY OF BEEF IN SPECIAL REGION OF YOGYAKARTA - Setiyono Setiyono; Andri Haryono Awalokta Kusuma; Rusman Rusman (Buletin Peternakan, 2017)
The aim of this research was to determine the effect of breed, age, and sex PO, SIMPO, and LIMPO’s cattles on physical and chemical quality also fatty acid’s profile. The sample were 180 cattles and this samples were divided into 3 groups, each group contain 3 different breeds (PO, LIMPO, and SIMPO). Every breeds divided into 2 subgroups based on sex and on age (1.5-2.0 years old; 2.5-3.0 years old; and more than 4.0 years old). Data were collected for slaughter’s weight, carcass’s weight, carcass’s percentage, and physical also chemical quality of Longissimus dorsi (LD) muscle. Data were analized using a complete randomized design (CRD) with factorial design: 3X3X2 factorials and subsequently continued with Duncan’s new multiple range test. The results showed that breed and age had very significant differences (P<0.01) on slaughter’s weight, carcass’s weight, and carcass’s percentage. Sex of PO, SIMPO, LIMPO had significant differences (P<0.05) on slaughter’s weight and carcass’s weight. Chemical quality of meat showed that age and sex had significant differences (P<0.05) on moisture and fat contents. The conclusion was breed of LIMPO produced more carcass than PO and LIMPO but PO had better chemical quality than SIMPO and LIMPO.